DESIGN OF HOUSEHOLD-SCALE BIODIGESTER FROM COW MANAGEMENT - Moch Reza Fauzy; Riza M Yunus; Asep Rachmat (Jurnal Mekanika dan Manufaktur, 2023)
Biogas is one solution to overcome community difficulties due to rising fuel prices and the scarcity of LPG gas, this technology can be immediately applied, especially for cattle breeders. Utilizing cow dung that is processed anaerobically in a digester which will produce methane gas as an alternative energy. In planning this household-scale biogas device, there are several components designed including a digester with a volume capacity of 400L with a filling capacity of 2/3 of the digester volume, the material used is HDPE plastic (High Density Polyethylene) and a holding capacity of 147 L which produces a flash time. fire for 20.01 minutes for 15 days of the fermentation process. Where the lowest pressure is obtained on the 3rd day with a pressure of 104.668,73 N/m2, and the maximum pressure is on the 12th day with a maximum pressure of 107.201,85 N/m2i. simulation using solidwork software results in the digester construction which is planned to be used because it has a fairly good level of security